2015
DOI: 10.1371/journal.pone.0137756
|View full text |Cite
|
Sign up to set email alerts
|

Using Serum Advanced Glycation End Products-Peptides to Improve the Efficacy of World Health Organization Fasting Plasma Glucose Criterion in Screening for Diabetes in High-Risk Chinese Subjects

Abstract: The efficacy of using fasting plasma glucose (FPG) alone as a preferred screening test for diabetes has been questioned. This study was aimed to evaluate whether the use of serum advanced glycation end products-peptides (sAGEP) would help to improve the efficacy of FPG in diabetes screening among high-risk Chinese subjects with FPG <7.0 mmol/L. FPG, 2-h plasma glucose (2h-PG), serum glycated haemoglobin A1c (HbA1c), and sAGEP were measured in 857 Chinese subjects with risk factors for diabetes. The areas under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The sensitivity of using FPG alone for detecting diabetes was 56.1%, which is consistent with several other cross-sectional studies. [ 18 19 ] However, the efficacy of FPG for diabetes screening has been questioned. Therefore, some studies have attempted to improve the efficacy of FPG in diabetes screening by introducing new strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of using FPG alone for detecting diabetes was 56.1%, which is consistent with several other cross-sectional studies. [ 18 19 ] However, the efficacy of FPG for diabetes screening has been questioned. Therefore, some studies have attempted to improve the efficacy of FPG in diabetes screening by introducing new strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, HbA1c may not be suitable for mass screening of large populations because it is relatively expensive. Our previous study demonstrated that the use of serum advanced glycation end products-peptides substantially improved the efficacy of FPG in diabetes screening among high-risk Chinese individuals,[ 19 ] for which a sensitivity of 91.2% was found by combined utilization of advanced glycation end products-peptides and FPG. Nevertheless, the efficacy of advanced glycation end products-peptides in the general population for diabetes screening is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our exclusion criteria should also minimize any vulnerability related to individual differences in systemic or ocular diseases and their treatment. Because protein carbonyls and AGEs have been found elevated in other patient groups, including those with diabetes mellitus, 43 , 44 such patients, as well as patients with other ocular diseases, were excluded from our study groups. In addition, our study participants did not have previous vitrectomy, endothelial keratoplasty, or cataract surgery, which have been suggested to increase oxidative stress in the anterior chamber.…”
Section: Discussionmentioning
confidence: 99%
“…It is similarly appealing to further determine as to whether the lack of correlation between blood and aqueous humor levels of protein carbonyls (different than AGEs that exhibited a positive correlation between blood and aqueous humor levels) may suggest a higher specificity as a glaucoma-related biomarker. Particularly respecting the relation of protein carbonyls or AGEs to other diseases, such as diabetes mellitus, 43 , 44 continued longitudinal analysis in larger and heterogeneous cohorts of patients, with or without glaucoma, should help proper calculation of biomarker sensitivity and specificity for clinical prediction of glaucoma and its progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AGE-P exhibits the same toxic activity as AGEs, and AGE-P has been recognized to be responsible for complications of diabetes such as diabetic nephropathy [ 11 , 12 ]. More importantly, a reliable and reproducible assay for determining the serum AGE-P concentrations has been successfully validated in previous studies [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%